Interaction between protokimberlite melts and mantle lithosphere: Evidence from mantle xenoliths from the Dalnyaya kimberlite pipe, Yakutia (Russia) - Ashchepkov, IV; Ntaflos, T; Spetsius, ZV; Salikhov, RF; Downes, H (2016)
© 2016 China University of Geosciences (Beijing).The Dalnyaya kimberlite pipe (Yakutia, Russia) contains mantle peridotite xenoliths (mostly lherzolites and harzburgites) that show both sheared porphyroclastic (deformed) and coarse granular textures, together with ilmenite and clinopyroxene megacrysts. Deformed peridotites contain high-temperature Fe-rich clinopyroxenes, sometimes associated with picroilmenites, which are products of interaction of the lithospheric mantle with protokimberlite related melts. The orthopyroxene-derived geotherm for the lithospheric mantle beneath Dalnyaya is stepped similar to that beneath the Udachnaya pipe. Coarse granular xenoliths fall on a geotherm of 35 mWm-2 whereas deformed varieties yield a 45 mWm-2 geotherm in the 2-7.5 GPa pressure interval. The chemistry of the constituent minerals including garnet, olivine and clinopyroxene shows trends of increasing Fe# (=Fe/(Fe + Mg)) with decreasing pressure. This may suggest that the interaction with fractionating protokimberlite melts occurred at different levels. Two major mantle lithologies are distinguished by the trace element patterns of their constituent minerals, determined by LA-ICP-MS. Orthopyroxenes, some clinopyroxenes and rare garnets are depleted in Ba, Sr, HFSE and MREE and represent relic lithospheric mantle. Re-fertilized garnet and clinopyroxene are more enriched. The distribution of trace elements between garnet and clinopyroxene shows that the garnets dissolved primary orthopyroxene and clinopyroxene. Later high temperature clinopyroxenes related to the protokimberlite melts partially dissolved these garnets. Olivines show decreases in Ni and increases in Al, Ca and Ti from Mg-rich varieties to the more Fe-rich, deformed and refertilized ones. Minerals showing higher Fe# (0.11-0.15) are found within intergrowths of low-Cr ilmenite-clinopyroxene-garnet related to the crystallization of protokimberlite melts in feeder channels. In P-f(O2) diagrams, garnets and Cr-rich clinopyroxenes indicate reduced conditions at the base of the lithosphere at -5 log units below a FMQ buffer. However, Cr-poor clinopyroxenes, together with ilmenite and some Fe-Ca-rich garnets, demonstrate a more oxidized trend in the lower part of lithosphere at -2 to 0 log units relative to FMQ. Clinopyroxenes from xenoliths in most cases show conditions transitional between those determined for garnets and megacrystalline Cr-poor suite. The relatively low diamond grade of Dalnyaya kimberlites is explained by a high degree of interaction with the oxidized protokimberlite melts, which is greater at the base of the lithosphere.